2008
DOI: 10.1021/jf073322w
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Compounds and Antioxidant Activity in “Early Potatoes”

Abstract: The antioxidant content and the antioxidant capacity of both hydrophilic and lipophilic antioxidant extracts from four "early potato" cultivars, grown in two different locations (Racale and Monteroni), were examined. There was a considerable variation in carotenoid content and weak differences in the ascorbic acid concentration of the examined cultivars of "early potato" and between the harvested locations. An increase in both methanol/water (8:2 v/v) and phosphate buffer soluble (PBS) free phenols (70%) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 44 publications
5
51
1
Order By: Relevance
“…Due to their high potassium content, potatoes are no longer stigmatized as a simple starch-containing vegetable in the context of the School Lunch Program Healthy Hunger-Free Act of 2010 but instead considered as a valuable source for the mineral [68,74]. Despite micronutrients such as vitamin C and selenium, the phenol fraction seems to be the most important contributor to the antioxidant capacity of potatoes [75].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high potassium content, potatoes are no longer stigmatized as a simple starch-containing vegetable in the context of the School Lunch Program Healthy Hunger-Free Act of 2010 but instead considered as a valuable source for the mineral [68,74]. Despite micronutrients such as vitamin C and selenium, the phenol fraction seems to be the most important contributor to the antioxidant capacity of potatoes [75].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Roberts et al [32] have reported that the consumption of unpeeled cooked potatoes significantly increases lipid metabolism and antioxidant activity in cholesterol-fed rats. Potato extracts also significantly inhibit the proliferation of human breast cancer cells, via MCF-7, in a dose-dependent manner [26]. Although potato is not known as a source of provitamin A, e.g., β-carotene and β-cryptoxanthin [37], some yellow-fleshed cultivars contain a noticeable amount of lutein or zeaxanthin.…”
Section: Introductionmentioning
confidence: 98%
“…Potato is a good source of polyphenolics and carotenoids, particularly the pigmented or coloured varieties (Brown, 2005;Camire, Kubow, & Donnelly, 2009;Lachman & Hamouz, 2005;Tsao, 2009). As such, the antioxidant activity of these components in potatoes has been a focus of past studies (Al-Saikhan, Howard, & Miller, 1995;Han, Sekikawa et al, 2006;Lachman & Hamouz, 2005;Lachman, Hamouz, Orsak, Pivec, & Dvorak, 2008;Lachman et al, 2009;Leo et al, 2008;Nara, Miyoshi, Honma, & Koga, 2006;Reddivari, Hale, & Miller, 2007;Singh & Rajini, 2008). In rat studies, anthocyanins from both the red and purple pigmented potatoes showed protective effects against D-galactosamine or acetaminophen-induced liver damage (Han, Hashimoto et al, 2006;Han, Sekikawa et al, 2006;Han, Shimada, Sekikawa, & Fukushima, 2007;Ohba et al, 2007).…”
Section: Introductionmentioning
confidence: 99%